2011
DOI: 10.1590/s0365-05962011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Sweet: estudo de 73 casos, com ênfase nos achados histopatológicos

Abstract: BACKGROUND: Sweet's syndrome refers to a set of cutaneous, systemic and histopathological alterations that occur in response to different stimuli, in a similar way to that occurring in erythema nodosum, erythema multiforme and leukocytoclastic vasculitis. The syndrome has been described in association with conditions such as infections, pregnancy, the use of certain medications and malignancy. OBJECTIVES: To evaluate the clinical and histopathological alterations occurring in this syndrome and to assess the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 18 publications
3
12
0
2
Order By: Relevance
“…In this study, we observed that Sweet syndrome was more frequent in the women, and the mean age at diagnosis was 53 years, consistent with the data described in the literature (10)(11)(12)(13). Our results failed to show significant differences in age and sex in the patients of Sweet syndrome with and without hematologic malignancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we observed that Sweet syndrome was more frequent in the women, and the mean age at diagnosis was 53 years, consistent with the data described in the literature (10)(11)(12)(13). Our results failed to show significant differences in age and sex in the patients of Sweet syndrome with and without hematologic malignancy.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, fever was notably more common than other clinical symptoms (24/37, 65%), with a higher incidence than that in some studies (11)(12)(13), emphasizing that fever exists as an important diagnostic criterion of Sweet syndrome (3,4). Our study obtained a positive association with arthralgia in only 5% of the patients, none of whom had Sweet syndrome with hematologic malignancy.…”
Section: Aml* Comparison Of Hemoglobin and Platelet Levels Between Ssupporting
confidence: 42%
“…We performed a literature search using PubMed with search terms "HIV AND Sweet" or "HIV AND Acute febrile neutrophilic dermatosis," and identified 17 other published cases from 1994 to 2020 of Sweet syndrome in patients with HIV infection ( Table 1). One of these cases is mentioned in the context of a larger study on histopathological findings, but no further supporting details were available for tabulation [3]. A review of the published cases highlights important unique proposed etiologies for Sweet syndrome in those living with HIV: immune reconstitution inflammatory syndrome (IRIS) in 25% of cases [6,13,17], AIDS-defining conditions (i.e., Kaposi sarcoma and pneumocystis pneumonia) in two cases [5,6], and abacavir therapy in one case [8].…”
Section: Discussionmentioning
confidence: 99%
“…The head, neck and upper extremities are favored in an often asymmetric distribution, but lesions can occur anywhere on the body. Histologically, extensive papillary dermal edema with a diffuse nodular and perivascular neutrophilic infiltrate is evident [7]. A peripheral leukocytosis with neutrophilia and elevated ESR and CRP can help narrow the diagnosis.…”
Section: Discussionmentioning
confidence: 99%